Agroecological Intensification: Potential and Limitations to Achieving Food Security and Sustainability - Mockshell, Jonathan Yaw; Villarino, Maria Eliza J. (Elsevier, 2019)
Food systems across the world are increasingly threatened by climate change, depletion and contamination of natural resources, increasing population, rapid urbanization and shifting diets. Sustainable agricultural practices that are referred to by the label “agroecology” have been promoted as one of the solutions to the challenges, which have a potential to contribute to attaining the Sustainable Development Goals of ending hunger and achieving food and nutrition security. However, there is disagreement regarding the question of whether agroecology can indeed provide a real solution to these challenges. Some argue that sustainable agricultural intensification practices, which rely on high external input use, are critical to increasing agricultural productivity and are preferable to a focus on agroecological intensification practices, which rely on use of biological processes within the farm. Based on an analysis of the literature on this controversy, this article examines the potential and limitations of agroecological intensification for achieving food and nutrition security.